Trends in the ʼLivingʼLaw Development in Russia: The Lawmaking of Other Authorities - ADYGEZALOVA, Gyulnaz Eldarovna; KURDYUK, Petr Mihajlovich (Journal of Advanced Research in Law and Economics, 2018)
This article defines key directions of the lawmaking development in modern states that are conditioned by peculiarities of the legal development of society. The Presidential, Governmental and other executive authorities have particular importance for the legal regulation. Lawmaking problems remain relevant both in legal science and legal activity. Currently, there are many controversial issues in this area, including the correlation between the federal and regional lawmaking, application of sociological methods in the lawmaking process, observance of legislative techniques, identification of law-forming interests and provision of the balance between them, problem of law conflicts, etc. In this article we drew our attention to two real-life problems of the modern lawmaking process in Russia. In the first place, it is a hierarchical violation of statutory enactments on legal force. Secondly, it is an improper provision of laws with by-laws. In our opinion, the trends in the lawmaking development manifested in the Russian legal system are a consequence of the following factors: political, social and economic situation in the society; the state position on the international stage; internal processes of the law system development. This research mainly aims to identify trends in the development of the modern law making in Russia.